The Interrogative Sentence in English and Buton Tomia Language - Ekhsan, Nur Syamsiyah; Rifanti, Rifanti (Actual Insight, 2023)
This research has analyzed some differences of interrogative sentences in English and Buton Tomia language in order to contribute positively in language learning and teaching. Researcher used qualitative methods. Data in this research obtained by using literature study and interview. The results of the analysis found that the similarities between interrogative sentences in English and Buton Tomia is that each sentence uses a subject, verb, and object. While the difference in the form of interrogative sentences in English and Buton Tomia is that each interrogative sentence (yes/no question) in English begins with an auxiliary verb in the Buton Tomia language does not use auxiliary verbs and the form of interrogative sentence (yes/no question) in the Buton Tomia language.